Analysis of the Non-Medical Waste Management System at Kabelota Donggala Hospital - Nurlina; Budiman; Baculu, Eka Prasetia Hati (Jurnal Riset Kualitatif dan Promosi Kesehatan, 2025)
Hospital waste management in Indonesia still faces obstacles, causing environmental and health impacts. A sustainable management system is needed, especially the non-medical waste processing process at the Donggala Kabelota Regional Hospital, including sorting, containerization, transportation and final processing. The type of research method used is a qualitative type aimed at describing the non-medical waste management system at the Kabelota Donggala Regional Hospital. This research was carried out through observation and interviews with six informants which were carried out from November to December 2024. The results of the research showed that from the results of interviews with 6 informants it was found that the process of sorting, storing and storing waste in temporary storage areas (TPS) did not meet the standards, while for the transportation and final processing variables it was in accordance with the standards of Minister of Health Regulation No. 7 of 2019, so that there is still a need for improvement and special attention from the hospital in terms of facilities and infrastructure as well as the non-medical waste management process starting from sorting, containerization, transportation and storage in temporary storage areas. The conclusions and suggestions from this research are that the management of non-medical waste at the Kabelota Donggala Regional Hospital for the processes of sorting, containing, storing waste in temporary storage areas (TPS) is not appropriate, while the transportation and final processing processes are appropriate. Therefore, it is recommended that hospitals further increase the capacity of human resources, especially waste management officers, as well as add and update facilities and infrastructure that support a better waste management system.